Heterologous expression and catalytic properties of codon optimized small-sized bromelain from MD2 pineapple - Rafida, Razali; Fikran Aranda, Fahrudin; Vijay, Kumar; Kazufumi, Takano; Cahyo, Budiman (MDPI, 2022)
Bromelain is a unique enzyme-based bioactive complex containing a mixture of cysteine proteases specifically found in the stems and fruits of pineapple (Ananas comosus) with a wide range of applications. MD2 pineapple harbors a gene encoding a small bromelain cysteine protease with the size of about 19 kDa, which might possess unique properties compared to the other cysteine protease bromelain. This study aims to determine the expressibility and catalytic properties of small-sized (19 kDa) bromelain from MD2 pineapple (MD2-SBro). Accordingly, the gene encoding MD2-SBro was firstly optimized in its codon profile, synthesized, and inserted into the pGS-21a vector. The insolubly expressed MD2-SBro was then resolubilized and refolded using urea treatment, followed by purification by glutathione S-transferase (GST) affinity chromatography, yielding 14 mg of pure MD2-SBro from 1 L of culture. The specific activity and catalytic efficiency (kcat/Km) of MD2-SBro were 3.56 ± 0.08 U mg−1 and 4.75 ± 0.23 × 10−3 µM−1 s−1, respectively, where optimally active at 50 °C and pH 8.0, and modulated by divalent ions. The MD2-SBro also exhibited the ability to scavenge the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) with an IC50 of 0.022 mg mL−1. Altogether, this study provides the production feasibility of active and functional MD2-Bro as a bioactive compound.